TINJAUAN HUKUM ISLAM PEMBERIAN REMISI TERHADAP NARAPIDANA KORUPSI - Rahadi, Andi Arifai; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research aims to find out an overview of Islamic law in granting remissions to corruption convicts. The problem in this research is that there are no regulations in Islamic law that regulate corruption cases, especially in Indonesia, which has a majority Muslim population. The research method used is library research. The data sources used are primary data sources and secondary data sources. The data collection method used is searching in journals, theses, books, statutory regulations and other literature related to journals. The results of this research show that, in Islamic law, granting remissions to convicts of criminal acts of corruption is a jarimah, corruption is not included in the area of ​​jarimah hudud nor is it included in the scope of jarimah qisas. But it is included in the area of ​​jarimah ta'zir. So in the judimah hudud, forgiveness (intercession) does not apply if the case has been brought to court. Meanwhile, for jarimah ta'zir, the possibility of providing forgiveness (intercession) is wide open, both by individuals and the government or ulil amri. Because Islam really appreciates people who repent and improve themselves. The principles of Islamic law, such as repentance and forgiveness, justice, transparency, accountability, restitution, and consideration of the public interest, have an important role in granting remission to corrupt convicts. These principles reflect the ethical and humanitarian values ​​in Islam.